Accumulation of the delivered treatment dose in volumetric modulated arc therapy with breath‐hold for pancreatic cancer patients based on daily cone beam computed tomography images with limited field‐of‐view. Issue 7 (5th June 2019) - Ziegler, Marc; Nakamura, Mitsuhiro; Hirashima, Hideaki; Ashida, Ryo; Yoshimura, Michio; Bert, Christoph; Mizowaki, Takashi
Abstract : Background and purpose: Inter‐fractional changes of the daily anatomy of the patient are a source of error in radiotherapy. This effect is especially present in the abdomen, where there are daily differences in the filling of the stomach or the intestines. This study investigated the impact of inter‐fractional changes of pancreatic cancer patients who underwent breath‐hold volumetric modulated arc therapy on the applied dose by using deformable image registration. Material and methods: Deformable image registration was used to determine a displacement field which maps the computed tomography (CT) used for treatment planning onto daily breath‐hold cone‐beam CT images with limited field‐of‐view (FOV) which were acquired at the beginning of every treatment fraction. Different B‐spline registration methods utilizing different metrics and regularizations were used and compared. The resulting deformed planning CT images were used to calculate the dose distributions on the anatomy of the day which can therefore be seen as a good estimation of the actually delivered dose during the treatment fractions. Additionally, the accumulated dose distribution was determined by accumulating all daily dose distributions using inverted deformation fields. The calculated dose distributions were then compared to the planned dose by comparison of dose volume histograms and dosimetric volumetric indices. Results: Best registration results were obtained using a gradient magnitude metric and a regularization of λ = 0.05. The accumulated dose distributions showed that the mean dose delivered to the clinical target volume was on median reduced by 0.61 Gy after 15 fractions from the planned dose. For the organs at risk, the accumulated dose distributions were still fulfilling all clinical goals for the patient cohort used in this study. It was found that rotating and shearing motions of the tumor led to a greater reduction in the mean target dose which correlated with the proximity of the target to the spine (r = 0.54, P  = 0.038). Conclusion: With the proposed method, it is possible to generate a deformed planning CT image which matches the anatomy of the day based on cone beam computed tomography images with a limited FOV and calculating the dose distribution of the day. The dosimetric impact of the inter‐fractional variations was small for most patients but showed larger deviations if the tumor is located in close proximity to the spine.